β-FeOOH Interlayer With Abundant Oxygen Vacancy Toward Boosting Catalytic Effect for Lithium Sulfur Batteries - Li, Yingying; Li, Xifei; Hao, Youchen; Kakimov, Alibek; Li, Dejun; Sun, Qian; Kou, Liang; Tian, Zhanyuan; Shao, Le; Zhang, Cheng; Zhang, Jiujun; Sun, Xueliang (Frontiers in Chemistry, 2020)
Due to the shuttle effect and low conductivity of sulfur (S), it has been challenging to 2 realize the application of lithium-sulfur (Li-S) batteries with high performance and long cyclability. In this study, a high catalytic active CNTs@FeOOH composite is introduced as a functional interlayer for Li-S batteries. Interestingly, the existence of oxygen vacancy in FeOOH functions electrocatalyst and promotes the catalytic conversion of intercepted lithium polysulfides (LiPS). As a result, the optimized CNTs@FeOOH interlayer contributed to a high reversible capacity of 556 mAh g -1 at 3200 mA g -1 over 350 cycles. This study demonstrates that enhanced catalytic effect can accelerate conversion efficiency of polysulfides, which is beneficial of boosting high performance Li-S batteries.